2020
DOI: 10.1186/s12891-020-03614-6
|View full text |Cite
|
Sign up to set email alerts
|

The acromioclavicular ligament shows an early and dynamic healing response following acute traumatic rupture

Abstract: Purpose: Symptomatic horizontal instability is clinically relevant following acute acromioclavicular joint dislocations. However, the intrinsic healing response is poorly understood. The present study sought to investigate timedependent healing responses of the human acromioclavicular ligament following acute traumatic rupture. Methods: Biopsies of the acromioclavicular ligament were obtained from patients undergoing surgical treatment for acute acromioclavicular joint dislocations. Specimens were stratified b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…The acute nature of the injury, associated with superior biological healing potential of the AC capsular tissue, may contribute to the explanation of this finding. 40 , 41 , 42 The potential of biological healing is most accentuated during the posttraumatic inflammatory and proliferative biological phases. 40 , 41 , 42 Thus, if an anatomically stable coracoclavicular situation is surgically established in this acute phase and ROM and load are limited—as performed in the acutely treated collective of the present study—the optimal biological healing potential may be leveraged and result in an acceptable integrity and stability of the AC joint capsule.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The acute nature of the injury, associated with superior biological healing potential of the AC capsular tissue, may contribute to the explanation of this finding. 40 , 41 , 42 The potential of biological healing is most accentuated during the posttraumatic inflammatory and proliferative biological phases. 40 , 41 , 42 Thus, if an anatomically stable coracoclavicular situation is surgically established in this acute phase and ROM and load are limited—as performed in the acutely treated collective of the present study—the optimal biological healing potential may be leveraged and result in an acceptable integrity and stability of the AC joint capsule.…”
Section: Discussionmentioning
confidence: 99%
“… 40 , 41 , 42 The potential of biological healing is most accentuated during the posttraumatic inflammatory and proliferative biological phases. 40 , 41 , 42 Thus, if an anatomically stable coracoclavicular situation is surgically established in this acute phase and ROM and load are limited—as performed in the acutely treated collective of the present study—the optimal biological healing potential may be leveraged and result in an acceptable integrity and stability of the AC joint capsule. Indeed, a radiologic evaluation of the AC and CC ligaments via magnetic resonance imaging demonstrated adequate AC-ligament consolidation following isolated CC stabilization in acute cases.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, present findings suggest that acute anatomical reconstruction of ACLC ruptures reliably leads to intrinsic ligamentous healing. A recent experimental study of the ACLC healing response defined the first 3 weeks after trauma as the acute phase [ 24 ]. Histomorphologically, reparative changes peaked as early as within the second week after ACLC rupture.…”
Section: Discussionmentioning
confidence: 99%
“…These studies confirmed that ligament healing progresses in typical overlapping phases of inflammation, proliferation and remodeling but shows fundamental differences between intra- and extraarticular ligaments. Recently, a fundamental histological study described the dynamic healing responses of the ACLC following acute traumatic rupture [ 24 ]. However, the authors are not aware of any study investigating the intrinsic healing characteristics of the human ACLC.…”
Section: Introduction/backgroundmentioning
confidence: 99%
“…Although this technique can be used in any AC joint dislocation to be treated surgically, it's especially advantageous in subacute or chronic AC joint dislocations after 3 weeks, when the healing potential of the native CC ligaments is diminished 18 .…”
Section: Technique Indicationsmentioning
confidence: 99%